Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/tbed.13792
|View full text |Cite
|
Sign up to set email alerts
|

Receptor utilization of angiotensin‐converting enzyme 2 (ACE2) indicates a narrower host range of SARS‐CoV‐2 than that of SARS‐CoV

Abstract: Summary Coronavirus (CoV) pandemics have become a huge threat to the public health worldwide in the recent decades. Typically, severe acute respiratory syndrome CoV (SARS‐CoV) caused SARS pandemic in 2003 and SARS‐CoV‐2 caused the ongoing COVID‐19 pandemic. Both viruses are most likely originated from bats. Thus, direct or indirect interspecies transmission from bats to humans is required for the viruses to cause pandemics. Receptor utilization is a key factor determining the host range of viruses w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
(38 reference statements)
0
25
0
Order By: Relevance
“…1b) with reported substitutions to G(2) I(7) N(3400) R(2) T(2) X (20). Deep mutational scanning of the RBD has shown that a mutation at S477 has a potential to affect the stability of the RBD as well as its binding to the ACE2 13 , whereas the structural effect of residue S477 in context of intra-RBD interactions is lesser understood while it is reported that the residues S477 and T478 in SARS-CoV-2 are responsible for specific and efficient interactions with hACE2 and provide an edge over SARS-CoV 14 . Therefore, we investigate the structural contribution of residue S477 in the RBD in order to understand its role inhACE2 binding.…”
Section: Introductionmentioning
confidence: 99%
“…1b) with reported substitutions to G(2) I(7) N(3400) R(2) T(2) X (20). Deep mutational scanning of the RBD has shown that a mutation at S477 has a potential to affect the stability of the RBD as well as its binding to the ACE2 13 , whereas the structural effect of residue S477 in context of intra-RBD interactions is lesser understood while it is reported that the residues S477 and T478 in SARS-CoV-2 are responsible for specific and efficient interactions with hACE2 and provide an edge over SARS-CoV 14 . Therefore, we investigate the structural contribution of residue S477 in the RBD in order to understand its role inhACE2 binding.…”
Section: Introductionmentioning
confidence: 99%
“…1b) with reported substitutions to G(2) I 7N(3400) R(2) T(2) X (20). Deep mutational scanning of the RBD has shown that a mutation at S477 has a potential to affect the stability of the RBD as well as its binding to the ACE2 13 , whereas the structural effect of residue S477 in context of intra-RBD interactions is lesser understood while it is reported that the residues S477 and T478 in SARS-CoV-2 are responsible for specific and efficient interactions with hACE2 and provide an edge over SARS-CoV 14 . Therefore, we investigate the structural contribution of residue S477 in the RBD in order to understand its role inhACE2 binding.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies to date have expressed different ACE2 orthologs on cells to measure the potential for SARS-CoV-2 infectivity. The results have shown some consistent patterns, such as the inability of Mus musculus ACE2 to interact with SARS-CoV-2 [2,24,26,32], (with the exception of mouse cells from the cornea [43]) or the relatively high infectivity afforded by pangolin ACE2 [6,26,28,29]. Results from other orthologs are more inconsistent.…”
Section: Discussionmentioning
confidence: 98%
“…in silico models that predict which orthologs would be likely to bind S-protein based upon amino acid residues known to interact with S-protein [4,9,[15][16][17][18][19][20][21][22][23][24][25], 2.) in vitro cell-based studies where viral infectivity of cells from different animals or cell-lines genetically modified to express different ACE2 orthologs are examined for interactions with S-protein (or its RBD) or infection with the virus or S-protein expressing pseudovirus [2,6,11,[26][27][28][29][30], 3.) and biochemical studies measuring the binding of S-protein with different ACE2 proteins [31,32].…”
Section: Introductionmentioning
confidence: 99%